The Cambridge companion to medieval romance - Krueger, Roberta L. (Cambridge University Press, 2000)
This Companion presents fifteen original and engaging essays by leading scholars on one of the most influential genres of Western literature, offering a clear introduction to a rich array of traditions and texts. An introduction, a chronology and a bibliography of texts and translations complete this lively, useful overview.